Anisotropic Charge Transport Enabling High‐Throughput and High‐Aspect‐Ratio Wet Etching of Silicon Carbide. Issue 8 (26th May 2022) - Shi, Dachuang; Chen, Yun; Li, Zijian; Dong, Shankun; Li, Liyi; Hou, Maoxiang; Liu, Huilong; Zhao, Shenghe; Chen, Xin; Wong, Ching‐Ping; Zhao, Ni
Abstract: Wet etching of silicon carbide typically exhibits poor etching efficiency and low aspect ratio. In this study, an etching structure that exploits anisotropic charge carrier flow to enable high‐throughput, external‐bias‐free wet etching of high‐aspect‐ratio SiC micro/nano‐structures is demonstrated. Specifically, by applying a catalytic metal coating at the bottom surface of a SiC wafer while introducing patterned ultraviolet light illumination from its top surface, spatial charge separation across the wafer is achieved, i.e., photogenerated electrons are channeled to the bottom to participate in the reduction reaction of an oxidant in the etchant solution, while holes flow to the top to trigger oxidation of SiC and subsequent etching. Such design largely suppresses recombination‐induced charge losses, and when used in combination with a top metal catalyst mask, the structure yields a remarkable vertical etching rate of 0.737 µ m min −1 and an aspect ratio of 3.2, setting new records for wet‐etching methods for SiC. Abstract : Silicon carbide is widely used in sensors, sustainable energy devices, and power electronic devices. However, its outstanding properties bring several challenges for wet etching techniques. This study presents a new strategy for high‐throughput and high‐aspect‐ratio wet etching of SiC, which is promising in fabricating novel wide‐bandgap semiconductor structures and devices.